2017
DOI: 10.1007/s13361-017-1621-3
|View full text |Cite
|
Sign up to set email alerts
|

Differential Fragmentation of Mobility-Selected Glycans via Ultraviolet Photodissociation and Ion Mobility-Mass Spectrometry

Abstract: The alternative dissociation pathways initiated by ultraviolet photodissociation (UVPD) compared with collision-induced dissociation (CID) may provide useful diagnostic fragments for biomolecule identification, including glycans. However, underivatized glycans do not commonly demonstrate strong UV absorbance, resulting in low fragmentation yields for UVPD spectra. In contrast to UVPD experiments that leverage covalent modification of glycans, we detail the capacity of metal adduction to yield comparatively ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 26 publications
0
35
0
Order By: Relevance
“…Several recent studies showed that the integration of radical-induced dissociation with LC or IMS separation can be a powerful approach for characterization of glycan mixtures, including those containing structural isomers. 1822…”
mentioning
confidence: 99%
“…Several recent studies showed that the integration of radical-induced dissociation with LC or IMS separation can be a powerful approach for characterization of glycan mixtures, including those containing structural isomers. 1822…”
mentioning
confidence: 99%
“…A third dimension can be added by perturbing the structure of native-like ions by increasing their internal energy. The most frequently used activation methods include collision-induced dissociation (CID) 34,35 , surface-induced dissociation (SID) 36,37 or ultraviolet photodissociation (UVPD) [38][39][40] . Other methods include electron capture dissociation (ECD) and electron transfer dissociation (ETD) 41 .…”
Section: Rd Dimension -Ion Reactivitymentioning
confidence: 99%
“…Moreover, they implemented synchrotron radiation laser producing extreme‐energy photons (10 nm < λ < 100 nm) to MS, to characterize the complex mixtures of oligosaccharides derived from red algae Porphyra umbilicalis . Also, to increase the UV photon adsorption to facilitate fragmentation, Morrison and Clowers used cobalt acetate as the adduct source .…”
Section: Advanced Dissociation Techniques For Glycomicsmentioning
confidence: 99%